Development of the BioSentinel Health Index: A Proposed Framework to Support Sustainable Management of Marinas - Alan Cottingham; Stephen Beatty; Jake Daviot; James R. Tweedley (Sustainability, 2026)
Marinas support recreational and commercial activities but can experience rapidly changing environmental conditions. Conventional monitoring may miss short-lived events, unrecognized contaminants and the combined biological effects of multiple stressors. Valvometry, the measurement of bivalve shell behaviour, provides continuous biological information on environmental variability and stress. This study developed and demonstrated the BioSentinel Health Index, a modular framework in which bivalve behaviour provides the primary assessment of biological condition, supported by separate evaluations of monitoring quality and management readiness. Minute-scale valve-gape data from the Mytilus galloprovincialis at Mandurah Ocean Marina, Western Australia, were analysed over 12 months. The Ecosystem Health module result was 87.9%, representing the proportion of valid observations for which mussels’ valves were classified as open, with all eight mussels exhibiting dominant periodicities close to 24 h. Mean valve gape showed a strong nonlinear association with water temperature, declining markedly above 22 °C. No validated environmental coordinated-closure alarm occurred during this study. Monitoring and Data module achieved 70.3%, while Management and Response module achieved 100%. The framework provides a transparent approach for integrating continuous biological monitoring with environmental management while keeping biological condition separate from monitoring and response capacity.